Mandarin mastery sign lingo: assessing the feasibility study of an interactive language learning card game with sign language features. - Dacir, Mariella P. Gatoc, Bernadette N. Luna, Jaime Elizabeth G. Saavedra, Mariel M. Sta. Ana, fatima M. Tomines, Maridel Joyce F. 4 0 16; 5
Because the game exposes participants to various linguistic and cultural expressions, it fosters empathy, cultural awareness, and mutual understanding. Furthermore, it oLers a substitute for conventional teaching techniques, enabling teachers to design more engaging, inclusive classrooms that accommodate diLerent learning preferences. Players are exposed to various linguistic and cultural expressions, fostering empathy, mutual understanding, and cultural awareness. Additionally, the game promotes the formation of crucial abilities necessary for academic, professional, and personal development, such as problem-solving, critical thinking, and teamwork. In addition to improving language acquisition and cross-cultural communication Mandarin Mastery Sign Lingo helps create a more capable, inclusive, and culturally conscious society by fostering students' intellectual and emotional growth.
Feasibility Study : (BSBA major Human Resource Management) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2